A BRIEF ANALYSIS ON THE “STARE DECISIS” OF ENGLISH JUSTICE AND ITS ATTEMPTED APPLICATION IN PERUVIAN LABOR JUSTICE - Martínez Morón, Alan César (2024)
This article aims to address the problems that have arisen with respect to the binding nature of the recent jurisdictional plenary sessions of Peruvian labor justice issued by the Supreme Court, since it would be attempting to partially replicate the figure of stare decisis, whose Exegesis dates back to the so-called English common law, to our system, which has its roots in the Roman Germanic system.